(untitled) (Journal of Computational Mathematics, 1985)
Under an assumption of distribution on zeros of the polynomials, we have given the estimate of computational cost for the resultant method. The result in that, in probability 1-μ, the computational cost of the resultant method for finding ε-approximations of all zeros is at most cd^2(log d+log1μ+loglog1ε), where the cost is measured by the number of f-evaluations. The estimate of cost can be decreased to c(d^2logd+d^2log1μ+dloglog1ε) by combining resultant method with parallel quasi-Newton method.